The application of Albert Bandura's Social Cognitive Theory: A Process in Learning Speaking Skill - Ilmiani, Aulia Mustika; Wahdah, Nurul; Mubarak, Mahfuz Rizqi (Ta'lim al-'Arabiyyah: Jurnal Pendidikan Bahasa Arab & Kebahasaaraban, 2021)
Albert Bandura's social cognitive theory is a theory that connects behaviorist and cognitive learning theory. This theory assumes that people can pay attention to others through observation, reinforcement, and modeling to learn new information and behavior. Based on this principle, the Arabic Language Education study program lecturer at IAIN Palangka Raya started learning maharah kalam by inviting students to review videos as a pilot, to be imitated and practiced. The purpose of this study is to describe the learning process of MahÄrah Kalam using social cognitive theory. Using descriptive qualitative methods, research data is generated through the process of observation, interviews and documentation. The results showed that there were four basic activities of learning maharah kalam using social cognitive theory. First, observing the pronunciation of a conversational sentence from a learning video. Second, remembering the pronunciation of the sentence either in the form of vocabulary or the question word used. Third, replicating pronunciation by imitating conversational sentences according to the learning video. Fourth, showing abilities by exploring conversations, as well as the pronunciation learned